Pozzolanic-Stabilised Mixture (PSM) for Residue sand as Road Base Materials - Jitsangiam, Peerapong; Nikraz, Hamid (Rajamangala University of Technology Lanna, 2009)
This study focuses on the viability of residue sand, a by-product from alumina refining, as road base materials in Western Australia. The soil stabilisation technique, a pozzolanic-stabilised mixture, was used to improve the properties of residue sand to satisfy minimum requirements for road bases. The intent of this stabilisation technique was to use potential by-products from industry in Western Australia as stabilising materials. The pozzolanic-stabilised mixture consisted of residue sand, Class F fly ash, a by-product from coal power stations, lime kiln dust, a by-product from the quicklime manufacturing, and cement. To investigate the quality of the stabilised material, a set of laboratory tests was performed. These included an unconfined compressive strength test, a California bearing ratio (CBR) test, and a resilient modulus test. Comparisons were made between the stabilised residue sand and the conventional road base material in West Australia (crushed rock added with 2% General Purpose (GP) Portland Cement). The principle of multi-layer elastic theory and the laboratory-based parameter were used in a pavement design exercise to determine allowable traffic loading. The results of this study show that the performance of the stabilised residue sand is superior to that of the conventional road base material. Our findings indicate that stabilised residue sand can provide improved performance when used as road base materials in Western Australia.